Emergency contraception and risk habits in a university population. (2nd November 2018) - Bauzà, M. L.; Esteva, M.; Molina, J.; Pereiró, I.; Ingla, M.; March, S.
Abstract: Objective: The aim of our study was to determine the self-reported prevalence of use of emergency contraception (EC), identify factors associated with EC use, and measure the prevalence in university students of pregnancy and abortion among users and non-users of EC. Methods: A cross-sectional descriptive study of university students using a self-administered questionnaire was carried out in 2016. The main dependent variable was EC use at any time. Independent variables included sociodemographic factors and factors related to harmful habits and sexual behaviour. Results: The study sample consisted of 1309 students (median age 20 years). Forty per cent of participants reported using EC; condom failure was given as the main reason. Variables associated with EC use in both men and women were illegal drug consumption and having had more than 10 sexual partners. In women, other factors associated with EC use were age at first coitus and non-centrist political views. The prevalence of pregnancy was 6.5% and the prevalence of voluntary abortion was 2.9%. This prevalence was similar for men and women and for EC users and non-users. Conclusion: EC use in university students was more likely in those who experienced contraceptive failure or used no contraception. There were differences between men and women. Those at higher risk of unplanned pregnancy were more likely to report EC use, which may explain why there was no difference in the rates of unwanted pregnancies between EC users and non-users.